Spiritual Influence Towards Relapse in Opioid Addicts in Therapy - MH, Nurulhuda; M, Najwa Haneem; CM, Khairi; D, Norwati; AA, Aniza (IIUM Medical Journal Malaysia, 2018)
Introduction: Substance abuse is both a social and public health problem with a substantial burden to society. Opioid dependence results in unemployment, crimes, family disruption, and transmission of diseases. In Malaysia, methadone maintenance therapy (MMT) has been introduced as a harm reduction method. However, relapse during treatment remains an issue to be resolved that hinders successful outcome in the therapy. Spirituality in the treatment of substance abuse disorders has yet to be fully explored. This study aims to examine how MMT clients who relapsed perceive spiritual deficits as an influence and association of spiritual practice with relapse. Methods: This is a cross-sectional study done from June-July 2016. All MMT clients undergoing therapy at 3 treatment centers in Terengganu, Malaysia who fulfilled the inclusion and exclusion criteria and consented were included in the study. A semi-structured questionnaire was filled via face to face interview and spiritual practice was assessed using Hatta Islamic Religiosity Scale. 121 questionnaires were assessed and data was analyzed using SPSS version 22 for quantitative data. Results: All respondents were males of Malay race and Islamic religion. Current relapse, defined as any episode of intake of opioid for the past one month after a period of abstinence was 34%. Only three out of 42 clients who relapsed had some spirituality theme in their perceived cause of their relapse. However, a significant majority of those relapsed had a spiritual practice score of less than the mean practice score. Conclusion: Relapse in opioid addiction remains high in those receiving MMT in Terengganu, Malaysia. Spirituality may have a subconscious influence towards relapse in addiction in MMT clients. Further effort should be taken to inculcate spirituality intervention effective to prevent relapse which may contribute towards achieving a more successful therapy outcomes.